2014
DOI: 10.3390/systems2040451
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Scaling in Complex Living Systems

Abstract: In this review I show that four major kinds of theoretical approaches have been used to explain the scaling of metabolic rate in cells, organisms and groups of organisms in relation to system size. They include models focusing on surface-area related fluxes of resources and wastes (including heat), internal resource transport, system composition, and various processes affecting resource demand, all of which have been discussed extensively for nearly a century or more. I argue that, although each of these theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
406
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(425 citation statements)
references
References 564 publications
(1,258 reference statements)
16
406
2
1
Order By: Relevance
“…Others claim that heterogeneous contingent factors are importantly involved in determining both the slopes and elevations of metabolic scaling relationships [10,16,23,32,[50][51][52]. As a point of departure for my discussion about the contingency versus constraints debate, I focus on published data showing that an extrinsic factor, namely ambient temperature, not only significantly affects the scaling of metabolic rate, but also does so in fundamentally different ways in ectothermic and endothermic animals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Others claim that heterogeneous contingent factors are importantly involved in determining both the slopes and elevations of metabolic scaling relationships [10,16,23,32,[50][51][52]. As a point of departure for my discussion about the contingency versus constraints debate, I focus on published data showing that an extrinsic factor, namely ambient temperature, not only significantly affects the scaling of metabolic rate, but also does so in fundamentally different ways in ectothermic and endothermic animals.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, like the MTE, cell-size theory predicts that changing temperature should affect the elevation of metabolic scaling relationships, but not their slopes (but see Section 3.2.2), which again is contradicted by the results described in this study. Most other models focused on the differential scaling of various resource-demanding processes and tissues or organs with different metabolic rates (see e.g., [10,38,52]) have yet to consider how ambient temperature may affect metabolic scaling slopes (but see discussion of dynamic energy budget theory below). Furthermore, a recent study has shown that temperature acclimation does not affect the size and metabolic rate of various organs of the prawn Macrobrachium tolmerum [78].…”
Section: Implications Of Results For Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…It would be of interest to explore whether there are alternative fits to the power-law N vs. N max or S vs. N functions. Even in cases where the functional relationship seemed incontestable in the past, such as the 3/4 power-law of metabolism, alternative fits suggested alternative theories to explain the origin of the pattern, not always suited for all organisms (9). An early explanation for log-normal distributions of abundance was that they arose from random demographic processes.…”
mentioning
confidence: 99%